2016
DOI: 10.1017/jfm.2016.192
|View full text |Cite
|
Sign up to set email alerts
|

Transitional structures in annular Poiseuille flow depending on radius ratio

Abstract: The transitional regime of incompressible pressure-driven flows inside an annular pipe is investigated using accurate direct numerical simulation in long computational domains. At marginally low friction Reynolds number Re τ , turbulence occurs in the form of intermittent localised structures. Different types of localisation are identified as the aspect ratio is varied from η = 0.8 to 0.1. These coherent structures vary from helical turbulence at η = 0.8 to streamwise-localised puffs at η = 0.1. They are respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 28 publications
4
37
1
Order By: Relevance
“…The laminar streamwise intervals have lengths of about 50h, consistently with those in pCf (Prigent et al 2002;Duguet et al 2010a;Brethouwer et al 2012). Such helical turbulence also occurs in aPf (Ishida et al 2016) with a similar value of the pitch angle. By reducing Re, the helical turbulence sustains until Re = 337.5 (Re τ = 24.0) and eventually decays at 325.…”
Section: Morphology Of Coherent Structuressupporting
confidence: 64%
“…The laminar streamwise intervals have lengths of about 50h, consistently with those in pCf (Prigent et al 2002;Duguet et al 2010a;Brethouwer et al 2012). Such helical turbulence also occurs in aPf (Ishida et al 2016) with a similar value of the pitch angle. By reducing Re, the helical turbulence sustains until Re = 337.5 (Re τ = 24.0) and eventually decays at 325.…”
Section: Morphology Of Coherent Structuressupporting
confidence: 64%
“…As mentioned earlier, for annular Poiseuille flow in the limit of radius ratio tending to one, the pattern is, not unexpectedly, in the form of intertwined helices [26][27][28]. In the planar case, the effects of spanwise-rotation on thresholds and pattern wavelengths have also been studied [88], but their variations turn out to be more complicated than for PCF due to a different shear wall-normal dependence.…”
Section: Other Planar Configurationsmentioning
confidence: 88%
“…On the other hand in the small gap limit, when this ratio tends to one and the curvature of the fluid layer tends to zero, a laminar-turbulent organization takes place in the form of turbulent helices translating in the gap, locally anticipating the oblique bands of the planar case. The crossover between the two regimes has been studied as a function of the radius ratio [26][27][28]. In the same way, fluid motion induced by steadily counter-sliding the cylinders along their axis, yields annular Couette flow (more easily implemented numerically [29] than approximated experimentally) that connects to PCF in the small gap limit in the same way as annular to plane Poiseuille flow.…”
Section: Contextmentioning
confidence: 99%
“…Hysteresis is also present between Re l and Re g . In terms of the transitional structure, our previous study 10 revealed smooth alternations, with dependence on h, of the localized turbulent patterns: helical turbulence, helical puff, and straight puff. Robust helical turbulence corresponding to the turbulent stripe in pPf has been identified for high h !…”
Section: Introductionmentioning
confidence: 86%
“…Ishida et al 10 focused only on transitional structures, and statistical properties in aPf were not examined. Hence, this article would describe statistical results including the friction factor.…”
Section: Introductionmentioning
confidence: 99%